Prevalence of Internet Gaming Disorder and Its Association With Personality Traits and Gaming Characteristics Among Chinese Adolescent Gamers - Liao, Zhenjiang; Huang, Qiuping; Huang, Shucai; Tan, Linxiang; Shao, Tianli; Fang, Ting; Chen, Xinxin; Lin, Shuhong; Qi, Jing; Cai, Yi; Shen, Hongxian (Frontiers in Psychiatry, 2020)
Background: Internet gaming is extremely popular, but some players engage in overuse, with negative outcomes. Knowing the prevalence rate and specific risk factors can provide a better understanding of the etiology of Internet Gaming Disorder (IGD). This study aimed to estimate the prevalence of IGD among Chinese adolescents and associate IGD with their personality traits and Internet gaming characteristics. Methods: A cross-sectional study design was utilized in this study. Participants were recruited from 34 provincial administrative districts in China and consisted of 6,379 adolescent game players aged 15–25 (males/females = 3,701/2,678, mean age: 19.35 ± 1.61). A self-report structured questionnaire containing questions regarding demographic information and Internet gaming use characteristics, the Video Gaming Dependency Scale, and the Chinese Big Five Inventory-brief version, was used in the study. Results: The prevalence of IGD among Chinese adolescent game players was 17.0%. All participants were divided into the IGD group (males/females=751/333, mean age: 19.74±1.85) or the non-IGD group (males/females=2950/2345, mean age: 19.27±1.54). Specifically, twelve factors were good predictors displaying significant associations with IGD (p<0.001), including neuroticism (β= 0.17), conscientiousness (β= 0.14), Internet gaming time per day (Hour) (β= 0.21), Internet gaming charge per month (Yuan) (β= 0.20), motive: escaping (β= 0.15), motive: sensation seeking (β= 0.13), motive: passing time (β= 0.08), motive: coping (β= 0.06), having one or two long-term game partners (β= 0.06), gender (β= 0.12), education (β= 0.04), and relationship status (β= 0.04). Conclusion: Specific personality traits (neuroticism, conscientiousness) and Internet gaming characteristics (time and game expenses, motives) were associated with IGD in our sample of Chinese adolescents.